Efficacy and safety of lithium and lamotrigine for the maintenance treatment of clinically stable patients with bipolar disorder: A systematic review and meta‐analysis of double‐blind, randomized, placebo‐controlled trials with an enrichment design. Issue 3 (26th April 2019) - Oya, Kazuto; Sakuma, Kenji; Esumi, Satoru; Hashimoto, Yasuhiko; Hatano, Masakazu; Matsuda, Yuki; Matsui, Yuki; Miyake, Nobumi; Nomura, Ikuo; Okuya, Makoto; Iwata, Nakao; Kato, Masaki; et al.
Abstract: Aim: Whether patients with adult bipolar disorder (BD) who have been clinically stabilized with lithium or lamotrigine should continue this medication is not established fully. This systematic review and meta‐analysis evaluated the efficacy and safety of lithium and lamotrigine for maintenance treatment in clinically stable patients with adult BD. Methods: This meta‐analysis included only double‐blind, randomized, placebo‐controlled trials with an enrichment design that selected patients who responded acutely to lithium or lamotrigine. Reports prior to November 15, 2018, were retrieved from the PubMed/Cochrane Library/Embase. The primary outcome was the relapse rate due to any mood episode at the study endpoint. Other outcomes were relapse rates due to a manic/hypomanic/mixed episode or depression at the study endpoint, discontinuation rate, death, and death by suicide. Risk ratios (RRs) (95% confidence intervals) were calculated. When the random‐effects model showed significant differences between groups, the number‐needed‐to‐treat (NNT) was estimated. Results: The search retrieved two studies regarding lithium (N = 218) and four evaluating lamotrigine (N = 706). Both drugs were superior to placebo for reducing the relapse rate due to any mood episode [lithium: RR = 0.52 (0.41‐0.66), P  <   0.00001, I 2  = 0%, NNT = 2.3 (1.6‐4.2); lamotrigine: RR = 0.81 (0.70‐0.93), P  =   0.004, I 2  = 0%, NNT = 8.3 (5.0‐25.0)] and all‐cause discontinuation. There were no significant differences in other outcomes between lithium or lamotrigine and the placebo groups. Conclusion: Both drugs showed benefit for preventing relapse in clinically stable patients with adult BD. However, the number of studies and patients in this analysis was small. Abstract : Study, patient, and treatment characteristics of the included double‐blinded, randomized placebo‐controlled trials of patients with bipolar disorder